2015
DOI: 10.1016/j.neuroscience.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous progesterone exacerbates running response of adolescent female mice to repeated food restriction stress by changing α4-GABAA receptor activity of hippocampal pyramidal cells

Abstract: Adolescent females are particularly vulnerable to mental illnesses with comorbidity of anxiety, such as anorexia nervosa (AN). We used an animal model of AN, called activity-based anorexia (ABA), to investigate the neurobiological basis of vulnerability to repeated, food restriction (FR) stress-evoked anxiety. Twenty-one of 23 adolescent female mice responded to the 1st FR with increased wheel running activity (WRA), even during the limited period of food access, thereby capturing AN's symptoms of voluntary FR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 77 publications
(108 reference statements)
3
20
0
Order By: Relevance
“…During these periods of elevated stress, transient inactivation of α4βδ-GABA A Rs enables animals to fully utilize NMDARs for hippocampal LTP induction, learning and memory formation (Shen et al 2010). As expected, exogenous progesterone, which metabolizes to allopregnanolone, exacerbates ABA vulnerability, characterized by food-restriction-evoked hyperactivity (Wable et al 2015a). Other candidate receptors that have yet to be analyzed for their correlation with wheel running include AMPA receptors, for which no data are yet available, and serotonin 5HT4 receptors, shown to lead to anorexia-like behavior when over-expressed in the prefrontal cortex (Compan et al 2015).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…During these periods of elevated stress, transient inactivation of α4βδ-GABA A Rs enables animals to fully utilize NMDARs for hippocampal LTP induction, learning and memory formation (Shen et al 2010). As expected, exogenous progesterone, which metabolizes to allopregnanolone, exacerbates ABA vulnerability, characterized by food-restriction-evoked hyperactivity (Wable et al 2015a). Other candidate receptors that have yet to be analyzed for their correlation with wheel running include AMPA receptors, for which no data are yet available, and serotonin 5HT4 receptors, shown to lead to anorexia-like behavior when over-expressed in the prefrontal cortex (Compan et al 2015).…”
Section: Discussionmentioning
confidence: 59%
“…While capturing the above symptoms of AN, ABA also reveals individual differences in vulnerability, quantified as the extent of food-restriction-evoked hyperactivity and weight loss (Aoki et al 2014; Chen et al 2016; Chowdhury et al 2013; Wable et al 2015a, b; Nedelescu et al 2016). Since excitability of the hippocampus is strongly linked to stress-induced anxiety (Shen et al 2007), and the extent of food-restriction-evoked anxiety is correlated with wheel running (Wable et al 2015b), we hypothesized that individual differences in wheel running might be influenced by the excitability of hippocampal neurons.…”
Section: Introductionmentioning
confidence: 99%
“…While most reviews consider the role of estrogen in anorexia nervosa, as it interacts with the dopamine, serotonin and neuropeptide systems within brains of individuals with anorexia nervosa (Casper et al, 2008; Kaye et al, 2009). In addition, the metabolite of progesterone, THP (3α,5α[β]-tetrahydroprogesterone, or 3αOH–5α [β]-pregnan-20-one), may increase an individual’s vulnerability to anorexia nervosa, through a Cl − flux-dependent desensitization of the ionotropic GABA (γ-aminobutyric acid) receptors expressed by CA1 pyramidal cells (Shen et al, 2007; Smith et al, 2009; Wable et al, 2015a). …”
Section: Anorexia Nervosamentioning
confidence: 99%
“…This involves the up-regulation of α4βδ-GABA A receptors (GABA A Rs) that occur adjacent to excitatory synapses formed onto dendritic spines in SR of the CA1. Quantitative electron microscopic immunocytochemistry reveals that the more that animals were able to suppress wheel running, higher is the frequency of α4βδ-GABA A Rs occurring adjacent to excitatory axo-spinous synapses of the dorsal hippocampal CA1 pyramidal cells (Wable et al, 2015a)(Fig. 6).…”
Section: Activity-based Anorexia (Aba) An Animal Model Of Anorexiamentioning
confidence: 99%
“…That study indicated that 20 and 40mg/kg of agmatine ameliorated ABA weight loss and plasma corticosterone increase suggesting a protective effect, possibly mediated via blockade of dopamine D2 and activation of 5-HT1A receptors [129]. A recent ABA study suggested that progesterone interacts with α4-GABA receptors and worsens wheel-running behavior [130], supporting the notion the increased hormone release during puberty is a vulnerability in some to develop AN [131]. Brain reward learning is altered in AN, behavior that has been associated with brain dopamine function suggesting that dopaminergic agents could ameliorate this dysfunction [132].…”
Section: Neurobiology Of Anmentioning
confidence: 99%